PRODUKSI SUBSTRAT FERMENTASI BIOETANOL SEBAGAI ALTERNATIF PEMANFAATAN LIMBAH PADAT KULIT SINGKONG di GNP SNACK KABUPATEN MAGELANG - , MUGI RAHAYU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The production process generates waste in the form of cassava chips cassava peel the inside and outside, as well as the hump of land that is not dangerous but it needs to be reduced. Cassava solid waste generated is large enough so that the cost to use it as a bioethanol fermentation substrate is also great. Part of the solid waste that has great potential to be used is cassava inner peel. Costs are required in the manufacture of bioethanol fermentation substrate that is part of the cassava peel, , NaOH, heating machine, hydrolysis, electricity and labor . Data taken solid waste includes solid waste composition ,the amount of waste produced and how to handle. This study was conducted aiming to identify the effect of concentration on the hydrolysis the sugar produced, so they can know the exact concentration of is used during hydrolysis process to produce sugar at optimal levels. Then the data is processed using descriptives statistical test, a test of homogeneity of variances and post hoc tests Tukey HSD multiple comparisons method to determine the average sugar content produced, the data variance and differences in concentrations that have real influence. Handling solid waste cassava peel performed in GNP snack industry with the highest intentsitas is taken by farmers every 3-4 days to be used as animal feed. The waste can be used as bioethanol fermentation substrate to produce a profit of Rp 3,375,000.00 per month.